2020
DOI: 10.1111/psyg.12534
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the relationship between ageing in place and successful ageing in elderly individuals

Abstract: Background With the increase in longevity in the world, successful ageing has become an important issue. This study aims to investigate the relationship between ageing in place and successful ageing in elderlies. Methods This study, which utilised a descriptive and relational‐screening model, was conducted with the participation of 370 individuals aged 65 and over who were registered in Family Health Centres in a city centre located in the eastern part of Turkey. Results The participating elderlies' Successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…We determined that the SAS mean score decreased as the education level decreased. The results obtained in previous studies 26,27 are in line with the results of our study. It can be stated that the low level of education of the older individuals results in passive attitudes in social life, inadequate use of stress coping mechanisms, inadequacy in their perception of social support, and thus, a decrease in the level of successful aging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We determined that the SAS mean score decreased as the education level decreased. The results obtained in previous studies 26,27 are in line with the results of our study. It can be stated that the low level of education of the older individuals results in passive attitudes in social life, inadequate use of stress coping mechanisms, inadequacy in their perception of social support, and thus, a decrease in the level of successful aging.…”
Section: Discussionsupporting
confidence: 93%
“…We found that as the monthly income level of individuals decreases, the level of successful aging also decreases. There are studies 26,[28][29][30][31][32][33][34][35] with parallel results in the literature. A low economic level may negatively affect individuals' quality of life, their likelihood of benefiting from health services, their future, and their mental state, thus affecting successful aging negatively.…”
Section: Discussionmentioning
confidence: 97%
“…A study demonstrated that females had a more positive attitude towards life 11 , and another study found that the rate of successful ageing was higher in females 10 . However, a study showed that gender has no effect on successful ageing 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Yalcinoz Baysal et al (2020) found higher education was one factor in satisfaction with aging in place and those who were married, owned a home, lived with a spouse, or had a higher income showed an increase in life satisfaction. Three populations of adults who are aging in place have been identified: balanced achievers, easygoing town keepers, and financial cautious worriers.…”
Section: Factors That Motivate and Support Aging In Placementioning
confidence: 99%